5,9,11-Trihydroxy-2,2-dimethyl-10-(30-methyl-2 butenyl)-3-(2”-methyl-3”-butenyl)pyrano[2,3a]xanthen-12(2H)-one from the Stem Bark of Calophyllum pseudomole - Mulyadi Tanjung (MDPI, 2016)
5,9,11-Trihydroxy-2,2-dimethyl-10-(3 0 -methyl-2 0 -butenyl)-3-(2”-methyl-3”-butenyl)- pyrano[2,3-a]xanthen-12(2H)-one (1) was isolated from the stem bark of Calophyllum pseudomole. The structure of 1 was established by spectroscopic analysis which included UV, IR, HRESIMS and NMRexperiments. Abstract: 5,9,11-Trihydroxy-2,2-dimethyl-10-(3′-methyl-2′-butenyl)-3-(2″-methyl-3″ butenyl)pyrano[2,3-a]xanthen-12(2H)-one (1) was isolated from the stem bark of Calophyllum pseudomole. The structure of 1 was established by spectroscopic analysis which included UV, IR, HRESIMS and NMR experiments.